Archaeological Gleanings from Aberfeldy, with Notices of Iron ’Yetts’ at Grantully, Stirling, and Edinburgh - Cash, C G (Proceedings of the Society of Antiquaries of Scotland, 1911)
Excavation of the stone circle at Tegarmuchd revealed some stones which had fallen including one with cup marks. A number of cup-marked boulders in the area are described along with a second stone circle at Shian. A yett is a Scottish type of interpenetrating iron bar gate. Examples from the castles of Grantully, Stirling and Edinburgh are described.